2020
DOI: 10.3174/ajnr.a6581
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Postmarket Analysis of the Neuroform Atlas Stent for Stent-Assisted Coil Embolization of Intracranial Aneurysms

Abstract: BACKGROUND AND PURPOSE:The Neuroform Atlas is a new microstent to assist coil embolization of intracranial aneurysms that recently gained FDA approval. We present a postmarket multicenter analysis of the Neuroform Atlas stent. MATERIALS AND METHODS:On the basis of retrospective chart review from 11 academic centers, we analyzed patients treated with the Neuroform Atlas after FDA exemption from January 2018 to June 2019. Clinical and radiologic parameters included patient demographics, aneurysm characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
1
11
1
Order By: Relevance
“…These findings may provide some reference for treatment decisions of a multi-disciplinary team. It has been identified that the size of intracranial aneurysms significantly affects the selection and treatment effectiveness of intracranial aneurysms (32)(33)(34)(35). Consistently, our analysis showed that intracranial aneurysms of size > 7 mm have a significantly higher risk of recurrence after coil embolization.…”
Section: Discussionsupporting
confidence: 85%
“…These findings may provide some reference for treatment decisions of a multi-disciplinary team. It has been identified that the size of intracranial aneurysms significantly affects the selection and treatment effectiveness of intracranial aneurysms (32)(33)(34)(35). Consistently, our analysis showed that intracranial aneurysms of size > 7 mm have a significantly higher risk of recurrence after coil embolization.…”
Section: Discussionsupporting
confidence: 85%
“…[5][6][7] Recently, low-profile stents were introduced to improve the navigability and success rate of the procedure because they can be delivered via 0.0165-or 0.017-inch microcatheters to access tortuous and smaller vessels. [8][9][10] Although the recommended use of the low-profile stents is for a parent artery with a diameter of either $2.0 or $2.5 mm, their off-label use for the treatment of aneurysms arising from smaller parent arteries has become more common. 11,12 However, little is known about the efficacy and safety of SAC using low-profile stents in vessels smaller than 2.0 mm.…”
mentioning
confidence: 99%
“…Two previous studies of SAC using the Atlas stent for treatment of naïve aneurysms have reported thromboembolic complication rates of 3.8 and 2.3%, respectively, and hemorrhagic complication rates of 0.8 and 0.8%, respectively ( 33 , 34 ). Reported thromboembolic complication rates in SAC studies using the Neuroform and Enterprise (Codman Neurovascular, Raynham, MA, USA) stents were 8.8 and 8.7%, respectively ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 96%